2021
DOI: 10.3389/fnins.2021.747726
|View full text |Cite
|
Sign up to set email alerts
|

A Multifaceted Approach to Optimizing AAV Delivery to the Brain for the Treatment of Neurodegenerative Diseases

Abstract: Despite major advancements in gene therapy technologies, there are no approved gene therapies for diseases which predominantly effect the brain. Adeno-associated virus (AAV) vectors have emerged as the most effective delivery vector for gene therapy owing to their simplicity, wide spread transduction and low immunogenicity. Unfortunately, the blood–brain barrier (BBB) makes IV delivery of AAVs, to the brain highly inefficient. At IV doses capable of widespread expression in the brain, there is a significant ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 166 publications
(360 reference statements)
0
25
0
Order By: Relevance
“…Potential strategies for increasing CNS delivery and selectivity are outlined in Figure 1 . They include different methods of administering/delivering the virus to the target tissue (IV, ICV, ICM, IT) and the engineering of a new generation of AAV capsids with enhanced delivery across the blood-brain barrier (BBB) to the adult primate CNS, while detargeting liver and other peripheral organs (Fischell and Fishman, 2021 ). Selecting optimized promoters and other tissue and cell-type specific control elements such as miRNA target sequences can provide an additional level of selectivity for finetuning the expression in transduced cells (Hordeaux et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential strategies for increasing CNS delivery and selectivity are outlined in Figure 1 . They include different methods of administering/delivering the virus to the target tissue (IV, ICV, ICM, IT) and the engineering of a new generation of AAV capsids with enhanced delivery across the blood-brain barrier (BBB) to the adult primate CNS, while detargeting liver and other peripheral organs (Fischell and Fishman, 2021 ). Selecting optimized promoters and other tissue and cell-type specific control elements such as miRNA target sequences can provide an additional level of selectivity for finetuning the expression in transduced cells (Hordeaux et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that this strategy led to protection against AβO-induced memory decline in wild-type mice and, significantly, to reversal of age-dependent memory impairment in APPswe/PS1ΔE9 mice. Potential advantages of the current approach include (i) the need for a single infusion of AAV-NUsc1 to achieve sustained brain expression of NUsc1, (ii) local brain expression and secretion of a single-chain antibody devoid of the Fc domain and, thus, less likely to induce aberrant immune/inflammatory responses, (iii) specific targeting of a particular subpopulation of AβOs that is highly toxic to synapses and neurons (15, 16), and (iv) being amenable to further development, including systemic administration of modified AAV vectors capable of effectively crossing the blood-brain barrier (36). Based on our current findings, we propose that development of AAV-NUsc1 represents a step towards reaching immuno-gene therapy for AD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, viral vectors have become a leading tool for gene therapy in humans. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The most commonly used viruses in pediatric clinical trials to date are adeno-associated viruses (AAVs), followed distantly by lentivirus and adenovirus. 20 Below, we explain the features that have made these vehicles the dominant vector in gene therapy research and development.…”
Section: Vehicles Virusesmentioning
confidence: 99%